2020
DOI: 10.1186/s43054-020-00024-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, laboratory and radiological assessment of skeletal maturation in children and adolescents with obesity

Abstract: Background Childhood obesity is related to multiple serious health problems and an enhanced risk of premature onset of diseases. The relation of skeletal maturation to obesity is undetermined. The study aims to evaluate skeletal maturation in children and adolescents with obesity, to correlate it with their anthropometric data, body fat content, BMI, fat mass and pubertal stage. Results Our study shows that obese children and adolescents have accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…While substantially greater levels of HDL and TG (p = 0.001, p = 0.001). Ibrahim et al [31] study reported that no substantial variation in lipid profile among obese children and controls. While Mohammed et al, [21] study found that LDL and serum TC had been substantially greater among children with obesity as contrasted to control.…”
Section: Asmentioning
confidence: 89%
“…While substantially greater levels of HDL and TG (p = 0.001, p = 0.001). Ibrahim et al [31] study reported that no substantial variation in lipid profile among obese children and controls. While Mohammed et al, [21] study found that LDL and serum TC had been substantially greater among children with obesity as contrasted to control.…”
Section: Asmentioning
confidence: 89%